Editorial Foreword IJSLS Volume 5 Number 1 - Irianto, Sulistyowati (The Indonesian Journal of Socio-Legal Studies, 2025)
This edition marks the end of 2025 and presents articles on seemingly unrelated themes but reveal various aspects of our current legal system and society. In several countries, including Indonesia, autocratic legalism has emerged as a governing practice. Indonesia's political elite do not obey the law, but instead change and manipulate the law in the name of the people to legitimise their power. Various policies continue to be enacted without a scientific basis or evidence-based data, and without considering their impact on people, especially the poor and vulnerable. State institutions are also systematically weakened because they operate without opposition when political parties form coalitions with the government, and there is no system of checks and balances. Rather than being obeyed, the law is used as a tool to maintain authoritarianism.